Potential of Trace Elements in Volcanic Highlands: Geogenic Sources and Their Implications for Productivity - Imas Masithoh Devangsari; Benito Heru Purwanto (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2025)
This study investigates the mineralogical composition and trace element potential of volcanic highland soils in Kejajar District, Wonosobo, Central Java, an area that has experienced long-term horticultural intensification. Volcanic Andisols in this region are known for high fertility but also carry risks of trace element accumulation due to complex mineralogy and intensive land use. Bulk powder X-ray diffraction identified feldspar, epidote, apatite, pyrite, and clay minerals, which may release essential (Zn, Cu, Fe, Mn) and toxic (Cd, Pb, As) elements through natural weathering and agricultural activities. Results show that horticultural soils on 9–15% slopes exhibited the highest HCl 25%-extractable P (224.70 mg/100 g). At the same time, shrubland soils also displayed high values (179.74 mg/100 g), indicating contributions from both fertilizer and geogenic sources. Although horticultural soils had higher chemical fertility, the shrubland maintained better physical (bulk density, 0.78 g/cm³) and biological quality (soil respiration, 36.48 mg C/kg/day). Productivity trends further highlight risks: cabbage yields declined by 41% (2020–2023), and potato production dropped by 11% (2017–2021). These findings demonstrate the dual role of geogenic and anthropogenic inputs in shaping soil quality and productivity. Sustainable management requires integrated strategies, including trace element monitoring, pH regulation, organic matter enhancement, and the use of low-contaminant fertilizers, to ensure long-term agroecosystem resilience in volcanic highlands.